Error Analysis of Academic Essays of Senior High School Students - Phyll Jhann Gildore; Azmeer Hasann Uka; Jonathan Yting (Journal Corner of Education, Linguistics, and Literature, 2023)
Students commit errors in their writing compositions due to their lack of English language proficiency and knowledge of the writing conventions. This study sought to analyze the errors committed by Senior High School (SHS) students of the University of Mindanao in their academic essays. The study utilized Corder’s error analysis to examine 100 academic essays of students. The results revealed that under the categories of errors, mechanics has the most problematic errors with 514 error counts (46.98%), followed by omission with 228 error counts (20.84%), addition with 190 error counts (17.37%), substitution with 153 error counts (13.99%), and permutation with nine error counts (0.82%), the least problematic category. The results further revealed that the SHS students are experiencing difficulties in applying grammatical and writing rules in their academic writing, such as appropriate usage of prepositions, omission and addition of affixations, proper structure of sentences, and substituting elements of sentences. The findings imply that consciousness-raising approaches to teaching grammar be used by teachers in school to improve the students’ knowledge of the English grammar and writing conventions.